Análisis del sistema artianexos s.a. en la empresa Antel de la ciudad de Babahoyo - Nathali Analy, Camino Mayorga (2019)
Technology forms a strategic role in organizational activities, which is why the present research carried out in the Antel company aims to analyze the “Artianexos SA” system because it presents difficulties when activating or canceling a computer service, in addition , the incorrect manipulation of the computing devices causes that the optimal operation of the system was not carried out efficiently causing the delay of the processes, for this, the research methodology used was the type of descriptive research; Deductive method; Survey technique through the implementation of a questionnaire, which allowed the collection of the necessary information to identify system anomalies with the help of the black box test